2014
DOI: 10.1371/journal.pone.0089273
|View full text |Cite
|
Sign up to set email alerts
|

Medieval Horse Stable; The Results of Multi Proxy Interdisciplinary Research

Abstract: A multi proxy approach was applied in the reconstruction of the architecture of Medieval horse stable architecture, the maintenance practices associated with that structure as well as horse alimentation at the beginning of 13th century in Central Europe. Finally, an interpretation of the local vegetation structure along Morava River, Czech Republic is presented. The investigated stable experienced two construction phases. The infill was well preserved and its composition reflects maintenance practices. The upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Significantly higher values were observed in the Wyrost and Kucharczyk method H(E-B) variable; (c) Group 2 (Western Pomerania) showed statistically significant differences between variables. Similar to group 1 (Silesia, Kuyavia, and Lubusz land), the Wyrost and Kucharczyk method H(E-B) variable had higher values; (d) the statistical analysis of group 3 (eastern Pomerania) showed no statistically significant differences between variables harbor cities (Eastern Pomerania) (Dejmal et al, 2014;Gręzak, 2007).…”
Section: Regional Comparison Of Results Within Historical Polish Terr...mentioning
confidence: 88%
See 1 more Smart Citation
“…Significantly higher values were observed in the Wyrost and Kucharczyk method H(E-B) variable; (c) Group 2 (Western Pomerania) showed statistically significant differences between variables. Similar to group 1 (Silesia, Kuyavia, and Lubusz land), the Wyrost and Kucharczyk method H(E-B) variable had higher values; (d) the statistical analysis of group 3 (eastern Pomerania) showed no statistically significant differences between variables harbor cities (Eastern Pomerania) (Dejmal et al, 2014;Gręzak, 2007).…”
Section: Regional Comparison Of Results Within Historical Polish Terr...mentioning
confidence: 88%
“…The older estimation methods (Vitt and Kiesewalter) indicated that horses from Western Pomerania, Silesia, and Kuyavia (north‐western, southern, and central Poland) in the Middle Ages were slightly taller than animals from the northern part of country (Eastern Pomerania). This may be explained by the different environmental conditions in these early medieval ducal strongholds (Silesia and Kuyavia, Western Pomerania) than in large medieval and harbor cities (Eastern Pomerania) (Dejmal et al, 2014; Gręzak, 2007). Gdańsk (Danzig) and Kołobrzeg (Kolberg) were located near the Baltic Sea, and their geographical and geopolitical locations as trade centers influenced the animal bone assemblages composition discovered in archeological sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, these in situ dung (stabling) layers (MU16a4 and 18b) could also have been deposited by horses as horseshoes were recovered from mid-13 th century contexts during the excavation of the outer ward at Elbląg (Fonferek in press), and documentary sources indicate that stud horses were more often stabled in the outer baileys of castles to ensure their safety (Ekdahl 1998). There are similarities between the formation of the in situ stabling layers (MU16a4 and 18b) at Elbląg and a 13 th century horse stable within a Moravian medieval bailey, Veselí nad Moravou, Czech Republic (Dejmal et al 2014), as in both cases the location of the stable is close to water as evident by flooding depositing alluvium.…”
Section: Discussionmentioning
confidence: 85%
“…Stable isotope analysis (O and H) of bone collagen and trace element analysis (Ba and Mg) of bone phosphate show that the horses consumed local water and consumed high Mg, Ba food, possibly grain and fed differently to other horses (Pluskowski et al submitted). At Veselí nad Moravou, Czech Republic, horses were fed meadow grasses as well as woody vegetation, millet, oat, and less commonly hemp, wheat and rye (Dejmal et al 2014), which is similar to the mixed grain and pasture evidence, probably hay from MU16a4 and 18b at Elbląg.…”
Section: Discussionmentioning
confidence: 96%
“…30 and 31). Its diet was different from domestic horses of the Middle Ages, which were partly fed on cereals (Dejmal et al 2014;Dvořáková 2007) and classical antiquity when their diet was enriched with wheat products (bread), legumes and even with wine and beer (Donaghy 2012).…”
Section: Methodsmentioning
confidence: 99%